Implementasi Kebijakan Transportasi Publik Melalui Program Bus Satria di Kota Kediri - Akmal Yuda Tama; Ertien Rining Nawangsari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research discusses urban public transportation in Indonesia, public transportation is an important factor as a basis for implementing sustainable urban development. This research focuses on a policy in the form of a program which is the result of a breakthrough from the Kediri City Government through the Kediri City Transportation Department regarding urban public transportation, namely the Kediri City Satria Bus Program to increase accessibility and mobilization of urban communities. This research is aimed at finding out the implementation of public transportation policies through the Kediri City Satria Bus Program. This research uses the Policy Implementation analysis model by David C. Korten using three research aspects, namely 1) the type of program which consists of clear objectives, the existence of policies taken to achieve the objectives, there is a budget for implementing the program, there is a strategy for implementation. 2) the implementing organization which consists of cognition or understanding of the policy implementer, the direction of the program implementer's response to implementation. 3) recipients of policies consisting of program accuracy, implementation, target and process. The research method used in this research is descriptive qualitative using data collection techniques in the form of interviews, observation and documentation. The results of this research show that the implementation of the Kediri City Satria Bus Program has been running and has been successful in accordance with the wishes of the Kediri City community, however there are several shortcomings felt by the city community as program users.